PROSPECTIVE TEACHERS' PERSPECTIVES ON PEDAGOGICAL CHALLENGES EXPERIENCED DURING WORK-BASED LEARNING - Margeviča-Grinberga, Ieva; Šūmane, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
This study investigates prospective teachers' perspectives regarding pedagogical issues and evaluates their readiness to address these challenges during instructional practice. The research investigates the experiences and perspectives of 67 students currently enrolled in teacher education programmes by employing a narrative content analysis methodology. The results point to several significant areas of concern among prospective teachers. Initially, classroom management emerged as a primary challenge, with many students expressing anxiety about efficiently managing diverse classroom dynamics and maintaining discipline. This problem indicates the need to pay more attention to classroom management strategies in study courses. Furthermore, the findings emphasize difficulties in effectively differentiating instruction to meet the diverse needs of learners. It was indicated that there is a need for more concentrated training in inclusive teaching methods since students voiced worries about their capacity to adjust teaching approaches to accommodate a variety of learning styles and abilities. The study suggests that prospective teachers are generally enthusiastic about their future careers but also recognize significant pedagogical challenges.  To properly prepare future educators for the realities of the classroom, these findings have implications for teacher education programmes. They indicate a need for a more specific focus on practical skills such as classroom management and inclusive teaching practices.